Experimental and Numerical Investigations of Wind-Induced Effects on Ground-Mounted Solar Panels at the WDS Facility - Massaad, Charly (Université d'Ottawa / University of Ottawa, 2019)
The usage of ground-mounted photovoltaic solar panels is increasing, and it is essential to fully understand the wind behavior and loading on the panels, since there is no specific code or guideline for their design in the present. In addition, the University of Ottawa and Carleton University recently developed a new facility, called the Wind Damage Simulator (WDS). This study will allow to understand the flow behavior in the facility, along with the effects of different blower rpm settings on the flow. A CFD study was also conducted, in order to examine the methodology and turbulence models suitable for the flow replicated in this facility, for future research. The newly developed Wind Damage Simulator (WDS) facility was used to examine wind-induced effects on two solar panels attached to a frame. The mean pressure coefficient distribution on the photovoltaic panels was examined for several wind angles of incidence (AOI) and wind speeds. The wind AOI considered were the 0°, 30°, 45°, 180°, 210° and 225°, along with wind speeds ranging from 14 m/s to 42 m/s, with increments of around 2 m/s. The experimental results showed fluctuations in the Cp distribution on the panels, due to the WDS wind flow being highly unstable. The 180° wind AOI led to the highest uplift mean Cp equivalent (Cpeq) value on the panels. The 45° and 180° wind AOI were found to induce a Cpeq of significantly higher magnitude on the first panel compared to the second panel, whereas the 0° and 210° wind AOI induced a significantly higher Cpeq magnitude on the second panel compared to the first panel Cpeq. Moreover, the CFD study provided pressure coefficient distribution on the panels and flow visualization when interacting with the panels surfaces. The LES Dynamic Smagorinsky subgrid scale model was found to be more suitable for the WDS numerical replication than the RANS shear stress transport k-ω turbulence model. The LES model showed the fluctuating pressure coefficients on the panels’ surfaces, induced by the swirls that were formed post interaction of the wind with the panels.
Keywords: solar panels; WDS facility; wind-induced pressure coefficient; computational fluid dynamics; wind test; LES; RANS